Analytical thinking skills included in Islamic education books for grades (6, 7, 8) of the basic stage in Jordan - Al-Obaysat, Iman Majali Abdullatif (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the degree of inclusion of analytical thinking skills in Islamic education books in Jordan, by analyzing the content of those books in order to answer the questions of the study, the study used the descriptive analytical method, and the tool was to build a list of analytical thinking skills, which included five skills The results of the study revealed the availability of analytical thinking skills to varying degrees in Islamic education books for grades (6, 7, 8) in Jordan, where the skill of The comparative and interviewing skill came in the second place, and a high percentage, and the observation skill came in the third rank, with a medium percentage, and my skills were similar and different, and the ranking in the last rank respectively and at a low percentage. The results showed that the Islamic education book for the sixth grade has It ranked first in the total number of iterations totaling (513) repetitions, where the share of the sixth basic book (188) repetitions, followed by the textbook of the eighth grade primary (167) repetitions, followed by the book of the seventh grade of the primary (158) repetitions, The study recommended Further studies to identify analytical thinking skills in books and other levels of study.